2020
DOI: 10.12659/msm.926432
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of MUC15 Is Correlated with Poor Prognosis of Pancreatic Cancer and Promotes Migration, Invasion, and Chemo-Resistance In Vitro

Abstract: Background MUC15, one of the hydrophilic glycoproteins that protect wet-surfaced epithelia, has been shown to be involved in tumorigenesis of various tumors. However, the mechanism of MUC15 in pancreatic cancer have not been revealed yet. Our study focused on investigating its clinical significance and function in pancreatic cancer. Material/Methods Using tissue microarrays and immunohistochemical staining, we evaluated MUC15 expression in 92 patients diagnosed with pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, the role of MUC15 in cancer is context-dependent and even opposite among different tumors. In some cases, MUC15 activates the ERK pathway, promoting the progression of glioma, thyroid and pancreatic cancer, leading to poor prognosis [18][19][20]. Additionally, high expression of MUC15 activates the Wnt/β-catenin signaling pathway, supporting invasion and migration in osteosarcoma [21].…”
Section: Ivyspringmentioning
confidence: 99%
“…However, the role of MUC15 in cancer is context-dependent and even opposite among different tumors. In some cases, MUC15 activates the ERK pathway, promoting the progression of glioma, thyroid and pancreatic cancer, leading to poor prognosis [18][19][20]. Additionally, high expression of MUC15 activates the Wnt/β-catenin signaling pathway, supporting invasion and migration in osteosarcoma [21].…”
Section: Ivyspringmentioning
confidence: 99%
“…MUC15 is reported to either facilitate or impair carcinogenesis in different cancer types. For example, MUC15 plays an oncogenic role in pancreatic, gastric, colon, and thyroid cancer [ 11 14 ]. Moreover, our previous study demonstrated that MUC15 downregulation correlated with advanced stage, poor differentiation, and metastasis of liver cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%